Avaliação da biodeterioração e das condições ambientais nos acervos da coleção teses e coletânea da Biblioteca Central da Universidade Federal de Santa Maria/RS - Arabidian, Lizandra Veleda (2013)
This paper presents a study of biodegradation and environmental conditions in the library Theses collections and UFSM Compilation in the Central Library of Universidade Federal de Santa Maria/UFSM. Hereby, looking emphasize the importance of the documental preservation, since it can be considered one of the fundamental functions for the conservation of library collections. The research studies the case of the Central Library, and, the environmental problems obtained from the data collections that were made the period from June/2012 to June/2013, by analyzing the existence of microorganisms in the environment and materials, as well as humidity conditions, lighting, ventilation and temperature. The diagnosis was made by direct observation of the situation of collections and through the obtained results it was possible to detect the needs for conservation and preservation of these environments, proposing a plan of actions to contribute to the preservation of documental and cultural heritage in our institution. For this task, were discussed theoretical references relevant to the subject, photographic surveys, as well as the use of a methodology directed to the collection of microbiological agents, being used as a basis for the identification and characterization of microorganisms that are deteriorating the collections. On the evaluation of microbiological contamination in the Library, it was found that fifteen different species of microorganisms were encountered on site. This evaluation was also conducted in a way that were defined the months with the highest incidence of humidity and temperature, getting to the conclusion that, internally, the microorganisms proliferate in greater quantities when there is a sudden change in temperature and humidity in the months from November to January with high temperature and in the months of June and July when there is excessive humidity. During the research, it was found that on the outside of the building, that is, the inner garden, there was more humidity than normal in the months of June, July and August 2012. This was followed by a graphical representation of the environment measurements made through specific instruments. After the identification and evaluation of biological agents that cause biodeterioration, the data were tabulated to evaluate contamination by microorganisms in the environment. The results demonstrate the need to use resources to correct high levels of moisture in the collections analyzed, temperature control and ventilation, as indicated the presence of bacteria and fungi, which could contribute to an unfavorable clinical goers library.It was concluded that regulation of a plan of preventive actions for preserving and conserving the documents would be important to recommend actions for library environment to prevent the appearance of problems that may affect the users and employees of the Central Library from UFSM.